2021
DOI: 10.1111/rda.13950
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E regulates bovine granulosa cell apoptosis via NRF2‐mediated defence mechanism by activating PI3K/AKT and ERK1/2 signalling pathways

Abstract: High-yield dairy cows are usually subject to high-intensive cell metabolism and produce excessive reactive oxygen species (ROS). Once ROS is beyond the threshold of scavenging ability, it can induce oxidative stress, imperilling the reproductive performance of cows. The study was to investigate the effects of vitamin E (VE) on H 2 O 2 -induced proliferation and apoptosis of bovine granulosa cells and the underlying molecular mechanism. Granulosa cells were pretreated with VE for 24 hr and then treated with H 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The PI3K/Akt signaling is associated with granulosa cell survival and death 5,44 . Multiple evidences have confirmed that activated PI3K/Akt pathway attenuated H 2 O 2 ‐induced oxidative stress and apoptosis in granulosa cells 25,43,45 . In this study, we found that IGF1 functioned as a classic upstream factor of the PI3K/Akt pathway, and kurarinone augmented the activation of this signaling through directly upregulating IGF1 expression.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The PI3K/Akt signaling is associated with granulosa cell survival and death 5,44 . Multiple evidences have confirmed that activated PI3K/Akt pathway attenuated H 2 O 2 ‐induced oxidative stress and apoptosis in granulosa cells 25,43,45 . In this study, we found that IGF1 functioned as a classic upstream factor of the PI3K/Akt pathway, and kurarinone augmented the activation of this signaling through directly upregulating IGF1 expression.…”
Section: Discussionsupporting
confidence: 53%
“…17 oxidative stress and apoptosis in granulosa cells. 25,43,45 In this study, we found that IGF1 functioned as a classic upstream factor of the PI3K/Akt pathway, and kurarinone augmented the activation of this signaling through directly upregulating IGF1 expression. Thus, we deduced that kurarinone targeted IGF1 to increase PI3K/Akt activation, protecting against H 2 O 2 -induced granulosa cell damage.…”
Section: Discussionmentioning
confidence: 57%
“…The other hub gene, AKT1 , is a key component of AKT/PI3K signaling pathways, which regulate a wide variety of cellular functions including cell proliferation, survival, metabolism, and angiogenesis. For example, AKT1 could regulate bovine granulosa cell apoptosis via PI3K/AKT and ERK1/2 signaling pathways to affect the reproductive performance of cows ( 51 ). The previous study also revealed that enhanced nutrition during early calfhood facilitates reproductive performance by regulating the hormones in the hypothalamic-pituitary-ovarian (HPO) axis ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…During follicular development, GC proliferation and apoptosis play a critical role in maintaining oocyte growth and ovarian functions [ 33 ]. There is accumulating evidence that the disturbance of O-GlcNAc regulation may induce alterations in the cell cycle and cellular proliferation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%